TPACK AND TEACHERS' DIGITAL COMPETENCE IN THE ERA OF INDUSTRY 4.0 - Yopi, Fanaturiza (International Journal Multidisciplinary (IJMI), 2024)
The impact of the Industrial Revolution 4.0 era extends to all aspects of human life, including education. Professional teachers play a crucial role in fostering effective learning and improving student outcomes. It is expected that teachers not only possess technological proficiency but also integrate it seamlessly into their daily teaching practices. Therefore, it is important to analyse how teachers' digital competence can overcome the challenges of era 4.0, as well as the role of Technological Pedagogical Content Knowledge (TPACK) in improving their competence. This study employs a literature review to analyse teachers' digital competence in era 4.0 and the associated challenges, as well as to explain the role of TPACK in improving their digital competence. This study employs a literature review to analyse teachers' digital competence in era 4.0 and the associated challenges, as well as to explain the role of TPACK in improving their digital competence. The study's results demonstrate that teachers face several challenges in improving their digital competencies, including transforming learning models, developing digital competencies, understanding students' individual needs, and integrating learning using current technologies such as artificial intelligence (AI) and internet-based learning applications. In the 4.0 era, TPACK plays a crucial role in enhancing teachers' digital competencies. TPACK provides a holistic approach that integrates three main dimensions of knowledge.